Comparing three ways to update Choquet beliefs - Eichberger, Jürgen; Grant, Simon; Kelsey, David (Economics letters, 2010)
We analyze three rules for updating neo-additive capacities. Only for Generalized Bayesian Updating is relative optimism the same for both updated and unconditional capacities. For updates of the other two, either the updated capacity is fully optimistic or fully pessimistic.
Gesehen am 02.03.2023